Determinant Factors Purchase Decision of Tokopedia with Brand Image as Intervening Variable - Hendy Tannady (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to examine the relationship between variables, especially variables brand ambassador, brand awareness, and brand image as an intervention. The data collection method in this research is purposive sampling method. Questionnaires were distributed to 131 respondents. The results of the questionnaire obtained were studied using path analysis. The results show that only brand awareness has no indirect influence between awareness of the purchase decision process